COMMUNITY EMPOWERMENT THROUGH ACCOUNTING EDUCATION TO IMPROVE FINANCIAL MANAGEMENT SKILLS - Rita J D Atawarman; Sheilla Tijahahu; Christi Salamba; Styven Talahatu; Suwek Seftiani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Improving Financial Literacy and Management Skills of Fisherman Groups Through Practical Accounting Education (Case Study: Seri Village, Ambon City) This community service program (PkM) aims to empower the fisherman groups in Seri Village, Ambon City, by enhancing their basic financial literacy and management skills using a practical accounting education approach. Weak financial management skills, especially in managing the fluctuating catch yields and income, are often the main obstacle to achieving economic stability and growth in the fisheries sector. The implementation method utilized was participatory and application-based training and mentoring, tailored to the income and expenditure patterns of the fishing community. The program involved a series of workshops that simplified basic accounting concepts, such as transaction recording. The effectiveness of the program was measured by comparing the results of a pre-test and post-test to gauge the increase in knowledge, as well as through observation and questionnaires to assess changes in financial management behavior. The results showed a significant increase in the understanding of financial management concepts among the Seri Village fishermen, evidenced by the improvement in the average post-test scores. Post-training mentoring also demonstrated positive changes in financial management practices, including the ability to set aside savings for boat/gear maintenance and the ability to control daily debt. In conclusion, practical accounting education is an effective and crucial instrument in community empowerment programs, particularly for the fishing sector. This PkM successfully equipped the fishermen with practical tools to make better and more planned financial decisions, directly contributing to the improvement of economic independence and the well-being of the fishing families.